Method and apparatus for determining relative positioning between devices - Pekhteryev, Georgiy; Rybalko, Serhii; Duan, Chunjie; Ye, Zhenzhen (2024)
Aspects of the subject disclosure may include, for example, transmitting, by a first transmitter of a first device, a first wireless signal, wherein the first wireless signal utilizes a first signaling technology, receiving, by a second receiver of the first device, a second wireless signal generated by a second device, wherein the second wireless signal utilizes a second signaling technology that differs from the first signaling technology, and transmitting, by a second transmitter of the first device, a third wireless signal responsive to receiving the second wireless signal, wherein the third wireless signal utilizes the second signaling technology, and wherein the third wireless signal enables the second device to determine location information associated with the first device and the second device. Other embodiments are disclosed.